“Producción urbana del cultivo de pimiento (capsicum annuum) con aplicación de abonos foliares y concentraciones de sustratos”. - Laverde Mena, Carlos Guillermo (2021)
The present research project was carried out in the parish head of the canton Valencia, belonging to the province of Los Ríos, the following objectives were set: Determine the substrate that presents the greatest increases in pepper production. Analyze the effect of foliar fertilizers in combination with substrates in the morphoagronomic and productive development of the plant. Carry out the benefit-cost analysis in each of the treatments under study. The Completely Random Design (DCA) was applied, with six treatments and three repetitions. The fertilizers used were, foliar: seaweed extract and humic acids, while the substrates used: chicken manure and slaughterhouse waste. The doses applied correspond to 1 kg / m2 of substrate. The vegetative development variables were evaluated: plant height at 15, 30 and 45 days, days to flowering; as well as in the harvest the production variables: number, length, diameter and weight of the fruit. The best results were obtained with the algae extract treatment with the poultry manure substrate, obtaining a plant height of: 44.99 and 62.17 at 30 and 45 days. Similarly, the shortest days to flowering with 19.33 days. Regarding the number of fruits, the extract of algae in combination with the substrate of chicken manure 31.33, length, diameter and weight of fruit with 14.09 and 6.32 cm, and 619.22 grams. The benefit / cost ratio with the best results was given with the treatment with seaweed extract and chicken manure substrate obtained higher values with USD. 0.88 for each monetary unit. Keywords: foliar fertilizers, substrate, pepper.